Characteristics and actions in high-risk COPD in unstable patients: The EPOCONSUL audit. - Myriam Calle Rubio; Bernardino Alcázar-Navarrete; José Luis López-Campos; Marc Miravitlles; Juan José Soler-Cataluña; Manuel E Fuentes Ferrer; Juan Luis Rodríguez Hermosa (PLoS ONE, 2025)
Objective To assess the clinical characteristics of high-risk COPD patients considered not stable for having had moderate or severe exacerbations of COPD in the three months prior to the audited review visit based on information extracted from the medical record documenting health interactions prior to the visit, and to analyse the therapeutic measures adopted at the follow-up visit. Methods This analysis used data from the EPOCONSUL audit, which evaluated outpatient care provided to COPD patients in respiratory clinics in Spain. This analysis included patients with a high-risk level of COPD and assessed patient non-stability at the audited visit defined based on moderate or severe exacerbations in the last three months that were reported at the follow-up visit. Results: 2008 high-risk patients were analysed. 30.1% of patients were considered unstable at visit. Factors associated with non-stability are dyspnoea (MRC-m) ≥2 (OR 1.5, 95% CI 1.18-1.92; p = 0.001), chronic bronchitis criteria (OR 1.61, 95% CI 1.15-2.25; p = 0.005), use of inhaled triple therapy (OR 1. 31, 95% CI 1.06-1.61; p = 0.010), use of oral therapies for COPD (OR 1.68, 95% CI 1.23-2.28, p = 0.001), use of long-term oxygen therapy (OR 1.36, 95% CI 1.07-1.73, p = 0.010), no follow-up in a specialist COPD clinic (OR 1.44, 95% CI 1.11-1.87, p = 0.006). In 10.1% of the patients considered not stable, because at the medical visit they were referred to have had moderate or severe exacerbations in the last three months, no action was taken at the visit and in 56% there was no change in COPD pharmacological treatment. Triple therapy was the most commonly prescribed therapy (68% in non-stable patients). Twenty-five percent of patients on triple inhaled therapy are also prescribed oral therapy. Conclusions One third of patients with high-risk COPD report exacerbations requiring treatment with antibiotics and/or systemic corticosteroids in the previous three months at the medical visit; and in more than half of these patients no changes in pharmacological treatment are made at the visit.